Investigating the psychometric properties of patient reported outcome measures in individuals with chronic diabetic neuropathic pain: prospective longitudinal cohort study protocol - Meeta, Poonam; Claydon, Leica Sarah; RamaKrishnan, Mani; Hendrick, Paul; Baxter, David G. (Taylor and Francis, 2015)
The prevalence of diabetes in New Zealand is estimated to be 7% of the total population. And higher incidence rates of peripheral neuropathic pain (NeP) in diabetic populations have been estimated (between 3 and 25%). A range of outcome measures (OMs) are used to evaluate a change following an intervention, in diabetic NeP clinical trials, but very few have adequate psychometric properties (PMPs) for key dimensions. This study aims to investigate the remaining PMPs (which have not been investigated so far) of established specific pain intensity and physical functional OMs in adults (⩾18 years) with chronic diabetic NeP.